PHYSICAL WATER QUALITY RESPONSE TO RAINFALL OF BETON KARST SPRING AT GUNUNGKIDUL REGENCY - YOGYAKARTA INDONESIA - M. Widyastuti; Sudarmadji Sudarmadji; Sutikno Sutikno; Heru Hendrayana (Faculty of Geography, Universitas Gadjah Mada, 2012)
Beton karst spring is located in the Ponjong sub District Gunungkidul Regency, at thewestern part of Bribin undergorund river catchment area. The purpose of this study are: 1) toknow the variations of rainfall and discharge in the research area, 2) to know thecharacteristics of the physical water quality of Beton spring and 3) to determine therelationship between the variations of the rainfall toward the discharge and the physicalwater quality of Beton spring. This study uses survey methods and the techniques of datacollection using sample by purposive sampling. The variables are rainfall (the depth andintensity), spring discharge and physical water quality of spring (EC, T, TDS, turbidity). Thedata analysis is conducted graphically and descriptively to explain the relationship betweenthe variations of rainfall to the discharge and physical water quality of spring. The resultsshow the rainfall has variations include the pattern, events and the amount of rainfall. Betonspring has high discharge variations. The physical water quality of the spring meets to thewater quality standards according to the Government Regulation number 82 years 2001. Thestrong correlation between rainfall variations to the discharge and the physical water qualityof Beton spring can be seen clearly. It is reflected from the high value of R2.